2008
DOI: 10.1002/ajmg.b.30748
|View full text |Cite
|
Sign up to set email alerts
|

Exclusion of linkage to chromosome 14q in a large South Tyrolean family with idiopathic basal ganglia calcification (IBGC)

Abstract: Familial Idiopathic Basal Ganglia Calcification (FIBGC) is a neurodegenerative syndrome that usually follows an autosomal dominant pattern of inheritance. Linkage to only one locus on chromosome 14q (IBCG1) has been described so far. We identified and characterized a large multigenerational Italian family from a population isolate with 14 FIBGC affected members. Linkage analysis excluded the IBCG1 locus, thus demonstrating further locus heterogeneity for this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Neurological and psychiatric symptoms of headache and depression are present in family member II:6. Most subjects with brain calcium calcification are clinically asymptomatic as some authors previously described [Geschwind et al, 1999; Oliveira et al, 2004, 2007; Preusser et al, 2007; Volpato et al, 2008, 2009]. IBGC in the Chinese family under this study was transmitted over three generations in an autosomal dominant fashion (Fig.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Neurological and psychiatric symptoms of headache and depression are present in family member II:6. Most subjects with brain calcium calcification are clinically asymptomatic as some authors previously described [Geschwind et al, 1999; Oliveira et al, 2004, 2007; Preusser et al, 2007; Volpato et al, 2008, 2009]. IBGC in the Chinese family under this study was transmitted over three generations in an autosomal dominant fashion (Fig.…”
Section: Discussionsupporting
confidence: 57%
“…Several IBGC families from Australia, China, Canada, and Germany were not linked to the chromosome 14q13 locus, indicating the existence of genetic heterogeneity [Brodaty et al, 2002; Oliveira et al, 2004]. Recently, a large South Tyrolean family with 14 subjects affected with basal ganglia calcification was not linked to the IBGC1 locus, either [Volpato et al, 2008]. Further analysis of the family identified a putative new locus for IBGC on 2q37 (IBGC2) [Volpato et al, 2009], although the analysis yielded a maximum −log10( P ‐value) for the NPL pair of 2.44 for marker D2S2973 , which is lower than the threshold NPL score of 3.18 for suggestive linkage.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Volpato et al 2008 reported a linkage study excluding a 14q chromosome region (locus IBGC1) in a large family with IBGC, originally from a population isolate in South Tyrol, Italy.…”
Section: Dear Editormentioning
confidence: 99%
“…Volpato et al 2008 should consider the possibility of facing a new syndrome that must be screened initially with a sensitive caryotype study, including microdeletion analysis and testing hypersensitivity to radiation and bleomycin. This could eventually explain the whole clinical heterogeneity in this pedigree and discard the possibility of comorbity.…”
Section: Dear Editormentioning
confidence: 99%
“…The original ‘IBGC2’ family from South Tyrol, Italy was included among the familial cases. Detailed information about the ‘IBGC2’ kindred has been previously published . Clinical data of the ‘IBGC2’ kindred and respective ratings of computed tomography (CT) scans can be found in Supplementary Tables 1 and 2.…”
Section: Methodsmentioning
confidence: 99%